Using PSNR parameter as a measurement tool in real-time estimation of multimedia information in WiMAX systems - Ivzhenko, Oleksii (Видавництво Львівської політехніки, 2012)
The given work is about of searching in field of transmission of multimedia data through wireless radio systems, based on OFDM-modulation technique, such like WiMAX. It's about ways to get the optimum scheme of adaptive coding and modulation.
Keywords: PSNR; BER; WiMAX; OFDM